Mercado e educação: a política do Instituto Ayrton Senna no município de Cabedelo/PB - Dias, Priscila dos Santos Ferreira (2009)
In the beginning of the XXIst century, Brazilian educational policy has been consolidated in the mercantilist scenario influenced by the global economy and this was not a characteristic phenomenon only in the private ambit. Approaching the theory of quasi-market it was evidenced a model of educational management focused in performance, developed in the public sphere. In this study, neoliberal ideas emerge with the creation of PDRAE, in FHC government, that potentializing the Minimum State contributes with the dissemination of non-governamental organizations to accomplish the competeces of State. In this context appears IAS – Ayrton Senna Institute, whose philosophy based on human development and praxis supported by the use of social technologies directed to education, making a partnership with public systems of teaching. Aiming an evaluative analysis of the performance of Cabedelo/PB SME – Municipal Teaching System, where since 2001 IAS works with its educational policy in the first phase of fundamental education through Programs that constitute the Win Web. This research presents results obtained in the mentioned town based on the IDEB – Basic Education Development Index and the Failure Rate (TR) according to INEP – Anísio Teixeira National Institute of Educational Researches and SIASI – Ayrton Senna Institute System of Information. Since the usage of instruments and technologies of social-educational intervention of IAS, as well as in the measurement of INEP indexes, it is explicit the relevance of considering the failure rate in the beginning grades as a variable of great importance to draw strategies of control and followup of the pedagogic processes, aiming the enhancing of the references of quality of teaching and consequent rise of IDH-E in the town, in the Management State logic. Conclusion points out that there was a significative improvement of the performance of Cabedelo/PB SME when analyzing from IDEB, but according to references of demographic indicators and Edudata Brasil the numbers are different in their database, thus, qualitatively compromising the obtained results.